Clinical Features and Prognosis of Double-Positive Anti-MDA5 and Anti-CCP Antibodies in Dermatomyositis: A Retrospective Study - Xu X; Zhu L; Li S; Wang G; Ge Y (Journal of Inflammation Research)
Xiayu Xu,1 Longyang Zhu,2 Sizhao Li,3 Guochun Wang,3 Yongpeng Ge3 1Department of Rheumatology and Immunology, The Second Affiliated Hospital of Hainan Medical University, Haikou, Hainan Province, People’s Republic of China; 2Peking University, China-Japan Friendship School of Clinical Medicine, Beijing, People’s Republic of China; 3Department of Rheumatology, The Key Laboratory of Myositis, China-Japan Friendship Hospital, Beijing, People’s Republic of ChinaCorrespondence: Yongpeng Ge, Department of Rheumatology, The Key Laboratory of Myositis, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of China, Email gyp2016@163.comObjective: To investigate the clinical features and prognosis of anti-melanoma differentiation-related gene 5 (MDA5) antibody and anti-cyclic citrullinated peptide (CCP) antibody double-positive dermatomyositis (DM) (MDA5+/CCP+ DM).Methods: A retrospective analysis of 264 consecutive cases of MDA5+ DM hospitalized from March 2018 to March 2022, and patients with anti-CCP antibodies were screened out. Patients from MDA5+/CCP- served as the control. Propensity score matching was used to compare the clinical features, as well as the treatment and survival outcomes between the two groups.Results: A total of 18 patients (6.8%) with MDA5+/CCP+ DM were identified. Gottron’s sign in 17 cases (94.4%), Heliotrope rash in 14 cases (77.8%), and skin ulcer in 5 cases (27.8%). Arthritis occurred in 10 cases (55.6%) and presented as the initial symptom in 6 cases (33.3%). Only 8 (44.4%) of the patients met the criteria for rheumatoid arthritis (RA). Interstitial lung disease (ILD) was diagnosed in 17 cases (94.4%), with non-specific interstitial pneumonia (NSIP) and organizing pneumonia (OP) combined with NSIP being the most predominant, as they presented in 6 cases (33.3%) each. Two of the ILD cases (11.1%) developed into rapidly progressive ILD (RP-ILD). Arthritis (55.6% vs 15.3%, p = 0.001) and malignancy (22.2% vs 0%, p < 0.001) were significantly more common in the MDA5+/CCP+ group compared to the MDA5+/CCP- group. The clinical manifestations of MDA5+/CCP+ DM with or without anti-Ro-52 antibody were not significantly different from those of the ILD type. During the follow-up period, there was no significant difference in survival between the two groups.Conclusion: More than half of the patients with MDA5+/CCP+ DM may present with arthritis as one of the initial symptoms. They may also have an increased risk of malignancy. For MDA5+ DM patients with positive anti-CCP antibodies, thorough screening for tumors is crucial to guide treatment and improve prognosis.Keywords: dermatomyositis, anti-MDA5 antibody, anti-CCP antibody, rheumatoid arthritis, interstitial lung disease